Asuhan Kebidanan Komprehensif Pada Ny. N Dengan Kek Dan Riwayat SC Di Puskesmas Suradadi Kabupaten Tegal - Anisya Ul Khoiriyah; Riska Arsita Harnawati; Istiqomah Dwi Andari (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
In comparison to the first and second trimesters of pregnancy, the prevalence rate of cake consumption during pregnancy is 35-75% greater in the third trimester globally. WHO also reports that persistent electricity shortages contribute to 40% of maternal mortality in underdeveloped nations. In 2017, malnourished pregnant women have a 60% increased risk of disease, including chronic exhaustion. To preserve the lives of mothers and newborns, the WHO has advised a maximum of 10% to 15% for sectio caesarea (SC) deliveries, although this number has increased globally. Situations surrounding KEK and History of Sc Due to the potential rise in maternal and fetal morbidity and mortality, this poses a significant obstetric risk. The goal of this case study is to get a realistic sense of what it will be like to care for Mrs. N as a full-service midwife at the Suradadi Health Center in Tegal Regency in 2022. By using Varney's 7-step midwifery care management and SOAP development data, during pregnancy, labor, postpartum, and babies. The OSOC method, which is an activity to accompany moms starting to be proclaimed pregnant until the postpartum period, was employed in this study as a case study methodology. The study's participants were expectant mothers. Mrs. N is 29 years old, has chronic energy deficiency, and has had Sc for less than two years. The outcomes during pregnancy were experiencing CED with an upper arm circumference of 22 cm and a history of Sc less than 2 years. Data collection was done from 17 October to 30 November 2022 utilizing interviews, observation, and recording.